Approach in Improving Student's Mathematical Understanding Abilities - Ammy, Putri Maisyarah (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
The purpose of this study was to determine whether learning with a problem-posing approach could improve students' mathematical understanding skills. The method used in this research is the literature review method, which is the activity of reviewing or exploring several articles, books, and documents (both printed and electronic), as well as data sources or other information that are considered relevant to the study. The data collection technique used in this research is the documentation method. The data analysis technique used was content analysis. Content analysis is used to obtain valid inferences and can be re-examined based on the context. To maintain the immutability of the assessment process and prevent, and overcome misinformation (a human misunderstanding that can occur due to a lack of researcher's knowledge or a lack of literature writers), inter-literature checks are carried out and re-read the literature and pay attention to the supervisor comments. Based on the results of data analysis from articles that have been carried out, it can be concluded that learning using the problem-posing approach can improve students' mathematical understanding abilities, marked by the increase in learning outcomes of students who learn using the problem-posing approach than students who use conventional learning.